Effectiveness of contemporary techniques for reducing livestock depredations by large carnivores. (13th December 2016) - Miller, Jennifer R. B.; Stoner, Kelly J.; Cejtin, Mikael R.; Meyer, Tara K.; Middleton, Arthur D.; Schmitz, Oswald J.
ABSTRACT: Mitigation of large carnivore depredation is essential to increasing stakeholder support for human–carnivore coexistence. Lethal and non‐lethal techniques are implemented by managers, livestock producers, and other stakeholders to reduce livestock depredations by large carnivores. However, information regarding the relative effectiveness of techniques commonly used to reduce livestock depredations is currently lacking. We evaluated 66 published, peer‐reviewed research papers that quantitatively measured livestock depredation before and after employing 4 categories of lethal and non‐lethal mitigation techniques (livestock husbandry, predator deterrents and removal, and indirect management of land or wild prey) to assess their relative effectiveness as livestock protection strategies. Effectiveness of each technique was measured as the reported percent change in livestock losses. Husbandry (42–100% effective) and deterrents (0–100% effective) demonstrated the greatest potential but also the widest variability in effectiveness in reducing livestock losses. Removal of large carnivores never achieved 100% effectiveness but exhibited the lowest variation (67–83%). Although explicit measures of effectiveness were not reported for indirect management, livestock depredations commonly decreased with sparser and greater distances from vegetation cover, at greater distances from protected areas, and in areas with greater wild prey abundance. Information on time duration of effects was available only for deterrents; a tradeoff existed between the effectiveness of tools and the length of time a tool remained effective. Our assessment revealed numerous sources of bias regarding the effectiveness of techniques as reported in the peer‐reviewed literature, including a lack of replication across species and geographic regions, a focus on Canid carnivores in the United States, Europe, and Africa, and a publication bias toward studies reporting positive effects. Given these limitations, we encourage managers and conservationists to work with livestock producers to more consistently and quantitatively measure and report the impacts of mitigation techniques under a wider range of environmental, economic, and sociological conditions. © 2016 The Wildlife Society. Abstract : We compared 66 studies that measured the effectiveness of lethal and non‐lethal techniques for reducing large carnivore attacks on livestock. Preventive husbandry and deterrents demonstrated the greatest effectiveness but widest variability while lethal removal showed moderate effectiveness with the lowest variation; however, more studies with consistent metrics of effectiveness are needed to overcome publication biases toward Canids in the United States, Europe, and Africa and studies reporting positive effects.